Bioprocess Potentials of Squalene from Thraustochytrids Microalgae for Nutraceuticals in New Normal Era Isolated from Indonesian Mangroves: A Review - Suhendra Suhendra; Tresya Pantoiyo; Sarah Fazlia; Endah Sulistiawati; Rachma Tia Evitasari (CHEMICA: Jurnal Teknik Kimia, 2021)
The covid-19 pandemic has been increasing people's awareness of good eating habits and consumption to maintain their health. Accordingly, the choice shifted more to consume nutraceutical and functional food to provide a beneficial impact. One of the essential and attractive nutraceuticals is squalene (C30H50). Squalene is a precursor for biosynthesis in all human steroids and has a long history as an essential compound in the pharmaceutical industry. A common source of this terpenoid comes from the liver oil of a deep-sea shark. However, the strategy for squalene production from liver sharks encountered environmental and political barriers due to strict nature protection regulations. The renewed scientific interest has found microalgae from the thraustochytrids family as a promising future source of squalene. Thraustochytrids is a group of Osmo-heterotrophic marine microalgae, which can be found commonly in mangrove are, has recently gained increased attention owing to its promising biotechnological potentials. As the country with the largest mangrove forest globally, Indonesia has the highest biodiversity potentials of Thraustochytrids. Unfortunately, the study on the potential of bioprocess technology using Thraustochytrids microalgae from Indonesian mangrove forests for squalene production has received less attention from researchers. Therefore, this paper presents Thraustochytrids' potential from Indonesian mangrove forests as a sustainable source of squalene production that can replace raw material from shark liver oil. This paper summarizes all selected strains used in the previous study and their operating parameters. Based on our review study, the most productive Thraustochytrid producing squalene comes from the Aurantiochytrium sp. 18W-13a–1, which operated in a temperature-controlled reciprocal 500 mL shaker of Sakaguchi flask (25 °C, 100 strokes min − 1,70 mm amplitude) and used nutrients of 2.0% glucose, 1.0% tryptone, 0.5 g /l yeast, and 50% artificial seawater (ASW). Compared to squalene from other sources (yeast, bacteria, and plants), Thraustochytrid can yield more squalene. Bioprocess engineering aspects and the general uses of squalene are also presented, including the notable developments in the adjuvant vaccine of Covid-19, anti-aging substance, and anti-cancer applications.